Uganda : : Native produce marketing ordinance - Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1934)
Colonial Office file relating to licences for the production and marketing of various crops by African producers in Uganda